Aging-Associated Alterations in Mammary Epithelia and Stroma Revealed by Single-Cell RNA Sequencing - Li, Carman Man-Chung; Shapiro, Hana; Tsiobikas, Christina; Selfors, Laura M.; Chen, Huidong; Rosenbluth, Jennifer; Moore, Kaitlin; Gupta, Kushali P.; Gray, G. Kenneth; Oren, Yaara; Steinbaugh, Michael J.; Guerriero, Jennifer L.; et al. (Cell reports (Cambridge), 2020)
Aging is closely associated with increased susceptibility to breast cancer, yet there have been limited systematic studies of aging-induced alterations in the mammary gland. Here, we leverage high-throughput single-cell RNA sequencing to generate a detailed transcriptomic atlas of young and aged murine mammary tissues. By analyzing epithelial, stromal, and immune cells, we identify age-dependent alterations in cell proportions and gene expression, providing evidence that suggests alveolar maturation and physiological decline. The analysis also uncovers potential pro-tumorigenic mechanisms coupled to the age-associated loss of tumor suppressor function and change in microenvironment. In addition, we identify a rare, age-dependent luminal population co-expressing hormone-sensing and secretory-alveolar lineage markers, as well as two macrophage populations expressing distinct gene signatures, underscoring the complex heterogeneity of the mammary epithelia and stroma. Collectively, this rich single-cell atlas reveals the effects of aging on mammary physiology and can serve as a useful resource for understanding aging-associated cancer risk. [Display omitted] •scRNA-seq captures aging-associated alterations in mammary epithelia and stroma•Identification of luminal and macrophage subpopulations reveals lineage complexity•Aging correlates with alveolar maturation and potential cellular functional decline•Aging is coupled to a potentially pro-tumorigenic and inflammatory microenvironment Using single-cell RNA-sequencing, Li et al. compare mammary epithelia and stroma in young and aged mice. Age-dependent changes at cell and gene levels provide evidence suggesting alveolar maturation, functional deterioration, and potential pro-tumorigenic and inflammatory alterations. Additionally, identification of heterogeneous luminal and macrophage subpopulations underscores the complexity of mammary lineages.